A glimmer of hope? Evaluation of time for non-genitourinary medicine physicians to diagnose HIV infection in patients presenting with HIV-related illness. (August 2013) - Clarke, E; Drew, O; Sundaram, S; Baker, A; Whale, J; Rowen, D; Patel, R
Summary: A study conducted in 2002–2003 at three UK south coast hospitals measuring the length of time for non-genitourinary medicine physicians to diagnose HIV when patients presented with an HIV-related illness, found a median time to diagnosis of four days with 70% of diagnoses being made within seven days. This retrospective cohort study of all patients newly diagnosed with HIV between 1 January 2010 and 31 December 2011 was conducted at the same three hospitals. Thirty-seven patients were newly diagnosed with HIV in non-genitourinary (GU) medicine inpatient and outpatient settings (24 men, 13 women), with a mean age of 43 years. The median time to diagnosis was one day (interquartile range of 0–4 days), with 81% of diagnoses made within seven days of first presentation. Late diagnosis of HIV remains a significant challenge, but delayed diagnosis in a patient admitted with an HIV-related illness is reducing in this setting.